Gladys Black letter to Nicholas S. Halmi, regarding bird sightings, March 6, 1977 - Black, Gladyset al (1977)
Letter from Gladys Black to Nicholas S. Halmi reporting her correspondence with Paul Jones regarding the impact of declining prey populations and the increased use of recreational vehicles on Snowy Owl populations. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly Report of spring 1977. Epson - sheet feed/flatbed